Quality of match for statistical matches using the Consumer Expenditure Survey 2011 and Annual Social Economic Supplement 2011 - Fernando Rios-Avila (Levy Economics Institute of Bard College, 2015)
This paper describes the quality of the statistical match between the Current Population Survey (CPS) March 2011 supplement and the Consumer Expenditure Survey (CEX) 2011, which are used for the integrated inequality assessment model for the United States. In the first part of this paper, the alignment of the datasets is examined. In the second, various aspects of the match quality are described. The results show appropriate balance across different characteristics, with some imbalances within narrow characteristics.
Keywords: C14; C40; D31; 330; Consumer Expenditure Survey (CEX) 2011; CPS-March Supplement; Statistical Matching; United States